Spina Bifida and Craniosynostosis New Perspectives and Clinical Applications - Kolarovszki, Branislav; Messina, Raffaella; Blè, Valeria (IntechOpen, 2021)
This book is a comprehensive overview of spina bifida and craniosynostosis with emphasis on new trends in the management of these diseases. Chapters on spina bifida cover such topics as the etiology and pathophysiology of caudal neural tube defects, the overall management of pediatric patients with spina bifida, surgical treatment, and urological and orthopedic care. The chapters on craniosynostosis present new technologies of surgical treatment, craniomaxillofacial corrective surgery, and telescoping techniques with multiple cranial osteotomies.